Design and Prototype of Electric Smart Stove - Sa'adilah - Rosyadi; Bayu Rahmat Setiadi; Joko Slamet Saputro (Journal of Electrical, Electronic, Information, and Communication Technology, 2021)
The prototype of the electric smart stove is an electric stove with briquette fuel from teak leaf waste. The thermoelectric module used is 12 units of a Peltier TEC-12706. Thermoelectric generators take advantage of the Seebeck effect with temperature differences from both sides of the Peltier will produce electrical energy. The developing prototype method of an electric smart stove is carried out in 4 stages. First stage, analyzing geometry requirements and smart stove shape. Second stage is the process making of an electric smart stove. Third stage, installation of a power plant. The fourth stage, measurement of electrical power output. Based on the experiment, it is found that the thermoelectric generator produces 1.31 volts of electrical energy with a delta T of 40 degrees Celsius. As the result, an electric smart stove has not been able to charge the battery because the electric energy produced tends to be small.